When does the Counsellor Self-Disclose and What are the In-Counselling Consequences - Mahrer, Alvin R.; Fellers, Gloria L.; Durak, Gary M.; Gervaize, Patricia A.; Brown, Sheila D. (Canadian Journal of Counselling and Psychotherapy, 2012)
Reviews of self-disclosure research cite the absence of data on the question of the actual in-counselling conditions under which counsellors self-disclose. On the question of the cli- ent consequences of counsellor self-disclosure, reviews of research cite the need for data from actual in-counselling sessions and the absence of data from experienced counsellors. An exhaustive search yielded a single full verbatim transcript by Dr. Sidney M. Jourard, perhaps the most eminent pioneer and exemplar of self-disclosure counselling. Analysis of this transcript suggested some unexpected hypotheses which invite more systematic study of the antecedents and consequences of self-disclosure as used by counsellors in both actual and analogue counselling sessions.